Comparison of the effectiveness of immersive and non-immersive virtual reality in the treatment of vertigo in patients with peripheral vestibular dysfunction: a systematic review and meta-analysis - Liu, Xiaoyi; Yang, Sha; Wang, Yiru; Tong, Ziwei; An, Xiao; Ren, Xiaoqing; Sun, Xu; Zhou, Zhicong; Wang, Hong; Liu, Xiaoying (Frontiers in Neurology, 2025)
BackgroundVertigo is the most common clinical manifestation in patients with peripheral vestibular dysfunction (PVD), and severe episodes may be accompanied by nystagmus, tinnitus, and hearing loss, which can seriously affect quality of life. Virtual reality (VR) technologies (immersive or non-immersive) play an important role in improving vertigo in patients with PVD, but the comparative effectiveness of VR technologies with different levels of immersion is unknown.ObjectiveTo investigate the effectiveness of VR technology at different immersion levels in reducing vertigo symptoms in patients with PVD.MethodPubMed, MEDLINE, Embase, Cochrane Library, Web of Science, CINAHL and 4 Chinese databases were systematically searched. Standardized mean difference (SMD) was calculated using RevMan 5.4 software, and risk of bias was assessed using the Cochrane Collaboration tool and Stata software. The review process was reported according to PRISMA.ResultsTwelve studies involving 600 participants met the inclusion criteria. The results indicated that both non-immersive and immersive VR significantly improved vertigo symptoms in patients with PVD; however, the immersive VR intervention demonstrated greater effectiveness (SMD = −2.08, 95% CI = −3.13 to −1.04, p < 0.001). Further subgroup analyses revealed that immersive VR intervention programs with a duration of ≤7 weeks (SMD = −2.73; 95% CI = −4.17 to −1.28, p < 0.001), a single intervention duration of <30 min/ times (SMD = −2.80, 95% CI = −4.89 to −0.70, p = 0.009), and a frequency of ≥5 times/week (SMD = −2.64; 95% CI = −4.91 to −0.38, p = 0.02) were more effective in alleviating vertigo symptoms.ConclusionImmersive VR has been shown to be more effective in alleviating vertigo symptoms in patients with PVD. Specifically, an immersive VR program that includes an intervention period of ≤7 weeks, a single intervention duration of <30 min, and an intervention frequency of ≥5 times/week is recommended for optimal improvement of vertigo symptoms. Further high-quality, multicenter randomized controlled trials are recommended to confirm the findings of this study. Healthcare professionals should focus on the individual differences of elderly patients with PVD and provide personalized VR vestibular rehabilitation programs for optimal rehabilitation outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025638469.